Anti-Wokeness, Hate Speech, and Rights Discourse Uphold the Status Quo: Current Realities in Education and Law - Jaffer, Safeera; Hudani, Ashna; Shariff, Shaheen (Critical Education, 2026)
The recent rise of anti-wokeness in Canada sustains and nourishes systemic oppression, while the radical roots of wokeness and legal rights discourse have been co-opted. Canada, a settler colonial state, relies on liberal values, including the rhetoric of multiculturalism and free speech, to uphold systems of power. Using critical race theory as a framework, we examine how rights discourse is not legally protected and contributes to the growth of hate speech and related hate crimes in Canada. As articulated by the Supreme Court of Canada in Canada (Human Rights Commission) v. Taylor, the Canadian Charter of Rights and Freedoms does not protect public dissemination of hate under the freedom of expression guarantee. Hateful discourse is not simply offensive; it has harmful material impacts, and this position is reaffirmed by the Supreme Court of Canada in the Saskatchewan (Human Rights Commission) v. Whatcott decision. Considering the role of anti-wokeness in the continued oppression of marginalized groups, we conclude by offering several recommendations for law and education to address this growing issue.